The role of epistemic communities in the formulation of foreign economic policy in Latin America: a literature review - Jiménez Peña, Gabriel (2014)
This paper is organized as follows. The introduction determines what Foreign Economic Policy is. Then, it builds a theoretical framework about Foreign Economic Policy formulation in developing countries, with a focus in Lain America. This discusses three different approaches: system-centered, society-centered and state-centered. Then, it explores literature about epistemic communities in Latin America in order to determine to what extent this has focus on Foreign Economic Policy formulation. Finally, it explores the importance of studying the role of epistemic communities in public agencies in charge of foreign economic relations in the region.